1989
DOI: 10.1007/bf01260504
|View full text |Cite
|
Sign up to set email alerts
|

?2-Adrenoceptor antagonists potentiate the anticonflict and the rotarod impairing effects of benzodiazepines

Abstract: Putative interactions between the specific alpha 2-adrenoceptor antagonist idazoxan and benzodiazepines (BDZs) were examined in two different rat conflict models; Vogel's drinking conflict test (VT) and Montgomery's conflict test (MT) (the elevated +-maze). In the MT, idazoxan (0.031 mg/kg) produced anxiogenic-like effects, which were counteracted both by the triazolo-BDZ alprazolam (APZ; 0.2 mg/kg) and the conventional BDZ diazepam (DIZ; 0.2 mg/kg). In fact, the anxiolytic-like effects of APZ were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
(36 reference statements)
2
5
1
Order By: Relevance
“…The present results are in concert with our earlier findings of a potentiative effect of the specific %-adrenoceptor antagonist idazoxan on BDZ induced anticonflict effects (S6derpalm and Engel, 1989). It therefore seems likely that it is the a2-adrenoceptor antagonistic properties of idazoxan and yohimbine that accounts for the potentiation observed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present results are in concert with our earlier findings of a potentiative effect of the specific %-adrenoceptor antagonist idazoxan on BDZ induced anticonflict effects (S6derpalm and Engel, 1989). It therefore seems likely that it is the a2-adrenoceptor antagonistic properties of idazoxan and yohimbine that accounts for the potentiation observed.…”
Section: Discussionsupporting
confidence: 88%
“…It was previously suggested that potentiative effects of %-adrenoceptor antagonists on the anticonflict activity of BDZs are mediated through blockade of a2-adrenoceptors located on NA neurons, so-called autoreceptors (S6derpalm and Engel, 1989). Blockade of such receptors increases the electrical activity of neurons originating in the principal NA nucleus of the brain, the Locus Ceruleus (LC) (see e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, imiloxan and piperoxan are apparently anxiogenic in the elevated X-maze (Handley & Mithani, 1984) and this latter agent is anxiogenic in the fear-potentiated startle test (Davis et al, 1979). On the other hand, whereas idazoxan has been reported by some authors (Handley & Mithani, 1984;Soderpalm & Engel, 1989) to be anxiogenic in the elevated X-maze test, others have found it to be without effect in this test (File, 1987;Moser, 1989). Similarly, 1-pyrimidyl piperazine, a metabolite of buspirone with a2-adrenoceptor antagonist properties, is not anxiogenic in this test (Moser, 1989), nor is the selective a2-adrenoceptor antagonist, atipamezole (Kauppila et al, 1991).…”
Section: Introductionmentioning
confidence: 83%
“…Other pharmacokinetic or pharmacodynamic properties must distinguish these two benzodiazepines. [Neuropsychopharmacology 8:305-314, 1993J in the treatment of panic disorder (Feighner et Eriksson et al, 1986;Kostowski et al, 1986;Soderpalm and Engel 1989) lap of [3Hlalprazolam onto other sites, a receptor au toradiographic approach (Kuhar et al 1985) was used in the present study. Previous investigations, aimed at analyzing the distribution of benzodiazepine receptors in the CNS, have principally involved the use of pHlflunitrazepam as the ligand of choice Kuhar 1979, 1980).…”
mentioning
confidence: 99%